ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI MINAT PERILAKU PENGGUNAAN SISTEM INFORMASI AKUNTANSI BERBASIS E-COMMERCE PADA APLIKASI SHOPEE ( Studi Empiris Pada Mahasiswa Akuntansi Universitas Islam Malang & Universitas Negeri Malang) - Riski Lasiba; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to analyze factors that influence the behavioral interest of users of e-commerce-based accounting information systems on the shopee application. This research is a quantitative study using primary data obtained from questionnaires and measured using a Likert Scale 1-5. The population in this study were students of the Islamic University of Malang and the State University of Malang. Sampling using purposive sampling with as many as 100 respondents. This data uses SPSS 25 analysis technique for windows. The results showed that Perceived ease of use, usefulness, and risk have a Simultaneous effect (F) on the behavioral interest of users of e-commerce-based accounting information systems in the Shopee application. Perceived ease of use positively impacts the behavioral interest of users of e-commerce-based accounting information systems on the Shopee application. Perceived usefulness positively affects the behavioral interest of users of e-commerce-based accounting information systems in the Shopee application. Perceived risk does not affect the behavioral interest of users of e-commerce-based accounting information systems in the Shopee application.Keywords: perceived ease of use, perceived usefulness, perceived risk, interest in user behavior, and accounting information systems